Digital goddess the unfiltered lessons of a female entrepreneur - Montgomery Brown, Victoria (Nashville HarperCollins Leadership, 2020)
With women leading only twenty-four Fortune 500 companies, female founders receiving only 2.2 percent of US venture capital, and the continued presence of sexual harassment and double standards, the gender gap continues to hinder the advancement of women in the professional world. In Digital Goddess, Montgomery-Brown--founder of Big Think, a collection of experts across all fields and disciplines that are either at the top of their field or disrupting it, shares her story in an entertaining and educational light. Told from the unique, female entrepreneurial perspective that unpacks all the hurdles other female founders may face in their own journey to the top, Montgomery-Brown shares the real-world lessons she's learned along the way, such as: Never lie to your investors, even when you just got arrested ; Raising money is a poker game--learn how to play ; The power and money still lie with men. Pretending it's not that way, or being angry about it, won't lead to success ; Your relationship with your co-founder is like a second marriage, so forget about keeping the personal out of the workplace ; The more authentic you are, and the more fun you have, the better your experience will be.
Includes bibliographical references (pages 211-214) and index.
Keywords: Businesswomen